2021
DOI: 10.1101/2021.02.16.431506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mixture of generative models strategy helps humans generalize across tasks

Abstract: Humans extract statistical regularities over time by forming internal representations of the transition probabilities between states. Studies on sequence prediction learning typically focus on how experiencing a particular sequence allows the underlying generative model to be learned. Here we ask what role generative models play when participants experience and learn to predict different sequences from a common generative family. Our novel multi-task prediction paradigm requires participants to complete four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Social learning is one of the core human capacities that have been vital in both growth and habitat expansion of human populations 8,9,33 . Previous research has shown that humans flexibly use various social learning strategies in response to the adaptive features of an environment 10,11 . Previous research has also used the exploration-exploitation tradeoff in information search 27,28 as a common platform to clarify computational algorithms underlying social learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social learning is one of the core human capacities that have been vital in both growth and habitat expansion of human populations 8,9,33 . Previous research has shown that humans flexibly use various social learning strategies in response to the adaptive features of an environment 10,11 . Previous research has also used the exploration-exploitation tradeoff in information search 27,28 as a common platform to clarify computational algorithms underlying social learning.…”
Section: Discussionmentioning
confidence: 99%
“…1 top). If such generalization is warranted (i.e., the old and new environments are structured or generated according to a common rule [10][11][12][13] , decision makers can solve the exploration-exploitation tradeoff in the new environments more efficiently. Although the question of knowledge generalizability has been discussed for many years 14,15 , it has remained largely unanswered because of the computational difficulty of quantifying its cognitive underpinnings in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the second group deal with the problem of how to use a structured representation for generalization purposes. These studies investigate how humans generalize through property induction (Kemp & Tenenbaum 2009), how they use learned reward functions for generalization during search tasks in spatially or conceptually correlated and graph-structured reward environments (Castañón et al 2021;Wu et al 2018Wu et al , 2020, and how they can learn how to generalize (Austerweil et al 2019).…”
Section: Rule/abstract Learningmentioning
confidence: 99%
“…Animals thrive in a constantly changing environmental demands at many time scales. Biological brains seem capable of using these changes advantageously and leverage the temporal structure to learn causal and well-factorized representations (Collins and Koechlin, 2012;Yu et al, 2021;Herce Castañón et al, 2021). In contrast, traditional neural networks suffer in such settings with sequential experience and display prominent interference between old and new learning limiting most training paradigms to using shuffled data (McCloskey and Cohen, 1989).…”
Section: Introductionmentioning
confidence: 99%